Azaheterocyclic diphenylmethanol chiral solvating agents for the NMR chiral discrimination of alpha-substituted carboxylic acids. Issue 57 (18th September 2020) - Li, Gao-Wei; Wang, Xiao-Juan; Cui, Dan-Dan; Zhang, Yu-Fei; Xu, Rong-Yao; Shi, Shuai-Hua; Liu, Lan-Tao; Wang, Min-Can; Liu, Hong-Min; Lei, Xin-Xiang
Abstract : Chiral azaheterocycle-containing diphenylmethanols with multiple hydrogen-bonding sites were described and used as NMR chiral solvating agents (CSAs). Highly resolved NMR spectra can be obtained directly in the NMR tube. Abstract : A series of small-membered heterocycle probes, so-called azaheterocycle-containing diphenylmethanol chiral solvating agents (CSAs), have been developed for NMR enantiodiscrimination. These chiral sensors were readily synthesized were inexpensive and efficiently used for the chiral analysis of alpha-substituted carboxylic acids. The sensing method was operationally simple and the processing was straightforward. Notably, we propose ( S )-aziridinyl diphenylmethanol as a promising CSA, which has excellent chiral discriminating properties and offers multiple detectable possibilities pertaining to the 1 H NMR signals of diagnostic split protons (including 25 examples, up to 0.194 ppm, 77.6 Hz). Its ability to detect the molecular recognition of fluorinated carboxylic acids were further investigated, with a good level of discrimination via the 19 F NMR spectroscopic analysis. In addition, an accurate enantiomeric excess (ee) analysis of the p -methoxyl-mandelic acid with different optical compositions have been calculated based on the integration of well-separated proton signals.